Toward a relational approach in global climate governance: Exploring the role of trust. (27th April 2021) - Marion Suiseeya, Kimberly R.; Elhard, Diana K.; Paul, Christopher John
Abstract: What role does trust play in global climate governance? For decades, claims of mistrust and distrust have dominated climate change policy arenas: doubts about climate change science and disagreements over rights and responsibilities related to mitigation, adaptation, loss, and damages undermine trust, impeding progress toward effective global climate action. And although frequently invoked in explanations of weak or failed climate action, there is limited research exploring the role of trust as a distinct concept in global climate governance. Here we seek to address this gap by developing a relational framework that focuses attention on how trust dynamics shape cooperation in four types of relationships: reliance, reciprocity, responsibility, and recognition. Applying this framework to the UNFCCC, we consider how efforts like expanded participation impact the relational landscape in global climate governance. We focus in particular on Indigenous Peoples and non‐state actors to demonstrate how the UNFCCC's efforts to address its legitimacy and credibility problems have neither adequately considered trust nor created opportunities to develop the transformative relationships needed for more effective climate governance. We suggest that greater attention to trust can help scholars and practitioners better understand how relational phenomena shape the landscape of governance possibilities. This article is categorized under: Policy and Governance > Multilevel and Transnational Climate Change Governance Abstract : This review explores the role of trust in global climate governance and develops a relational framework that focuses attention on how trust dynamics shape cooperation in four types of relationships: reliance, reciprocity, responsibility, and recognition. This framework is applied to the UNFCCC to evaluate how efforts such as expanded participation impact the relational landscape in global climate governance. Greater attention to trust can help scholars and practitioners better understand how relational phenomena shape the landscape of governance possibilities.